Sleep duration, vital exhaustion and perceived stress among pregnant migraineurs and non-migraineurs - Qiu Chunfang; Frederick Ihunnaya O; Aurora Sheena K; Williams Michelle A; Gelaye Bizu; Cripe Swee (BMC, 2010)
Abstract Background Migraine has been associated with sleep disorders in men and non-pregnant women, but little is known about sleep complaints among pregnant migraineurs. Methods A cohort of 1,334 women was interviewed during early pregnancy. At the time of interview we ascertained participants' migraine diagnosis status and collected information about sleep duration before and during early pregnancy, daytime sleepiness, vital exhaustion and perceived stress during early pregnancy. Multivariable logistic regression procedures were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) of short/long sleep duration, excessive daytime sleepiness, vital exhaustion and elevated perceived stress associated with a history of migraine. Results Approximately 19.4% of the cohort (n = 259) reported having a medical diagnosis of migraine prior to the study pregnancy. Compared with women without migraine, the multivariable-adjusted ORs (95% CI) among migraineurs for short sleep duration before and during early pregnancy were 1.51 (1.09-2.09), and 1.57 (1.11-2.23), respectively. The corresponding OR (95% CI) for long sleep duration before and during pregnancy were 1.33 (0.77-2.31) and 1.31 (0.94-1.83), respectively. A modest and statistically insignificant association between migraine history and excessive daytime sleepiness in early pregnancy was noted (OR = 1.46; 95% CI 0.94-2.26). Migraineurs had an increased risk of vital exhaustion (OR = 2.04; 95% CI 1.52-2.76) and elevated perceived stress (OR = 1.57; 95% CI 1.06-2.31). Observed associations were more pronounced among overweight migraineurs. Conclusions These data support earlier research documenting increased risks of sleep disorders among migraineurs; and extends the literature to include pregnant women. Prospective studies are needed to more thoroughly explore factors that mediate the apparent migraine-sleep comorbidity among pregnant women.